KEDUDUKAN BARANG BUKTI DALAM PERKARA PIDANA DITINJAU BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Julius Bernat Hasibuan (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTIn the Criminal Procedure Code, the evidence is not regulated in it but in the Criminal Procedure Code, the term evidence, also known as the term evidence, it appears that the evidence is not mentioned as included in one of the valid evidences. In other words, evidence is not a proof, questions can arise from here regarding the position of